2022
DOI: 10.3390/molecules27123840
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile and Antioxidant Capacity of Dabai (Canarium odontophyllum L.): Effect of Origin and Fruit Component

Abstract: In the present work, the influence of geographical location on the fatty acid profiles, antioxidant potential, as well as cytotoxicity of edible dabai fruit fractions (kernel, skin, and pulp) were analyzed. The fatty acid profiles were determined by Gas Chromatography (GC), and the antioxidant activity was quantified with free 2,2-diphenyl-1-picr/ylhdrazyl, while the cytotoxicity was assessed by the brine shrimp lethality test. The results showed that the samples from Sibu, Serian, and Kapit geographical locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…DDP, rich in anthocyanin and syringic acid, significantly lowers cholesterol, low-density lipoprotein, and β-hydroxy β-methylglutaryl-CoA (HMG-CoA) reductase, a rate-controlling enzyme of a metabolic pathway that produces cholesterol. A study by Salleh et al [ 7 ] revealed the excellent antioxidant capacities of edible dabai fruit components such as dabai kernel, skin, and pulp. Dabai kernel also has a high content of dietary fiber, up to 22%, which is good for lowering type 2 diabetes and the risk of heart disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…DDP, rich in anthocyanin and syringic acid, significantly lowers cholesterol, low-density lipoprotein, and β-hydroxy β-methylglutaryl-CoA (HMG-CoA) reductase, a rate-controlling enzyme of a metabolic pathway that produces cholesterol. A study by Salleh et al [ 7 ] revealed the excellent antioxidant capacities of edible dabai fruit components such as dabai kernel, skin, and pulp. Dabai kernel also has a high content of dietary fiber, up to 22%, which is good for lowering type 2 diabetes and the risk of heart disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%